Pioglitazone Represents an Effective Therapeutic Target in Preventing Oxidative/Inflammatory Cochlear Damage Induced by Noise Exposure - Paciello, Fabiola; Fetoni, Anna Rita; Rolesi, Rolando; Wright, Matthew B.; Grassi, Claudio; Troiani, Diana; Paludetti, Gaetano (Frontiers in Pharmacology, 2018)
Recent progress in hearing loss research has provided strong evidence for the imbalance of cellular redox status and inflammation as common predominant mechanisms of damage affecting the organ of Corti including noise induced hearing loss. The discovery of a protective molecule acting on both mechanisms is challenging. The thiazolidinediones, a class of antidiabetic drugs including pioglitazone and rosiglitazone, have demonstrated diverse pleiotrophic effects in many tissues where they exhibit anti-inflammatory, anti-proliferative, tissue protective effects and regulators of redox balance acting as agonist of peroxisome proliferator-activated receptors (PPARs). They are members of the family of ligand regulated nuclear hormone receptors that are also expressed in several cochlear cell types, including the outer hair cells. In this study, we investigated the protective capacity of the, pioglitazone, in a model of noise-induced hearing loss in Wistar rats and the molecular mechanisms underlying this protective effects. Specifically, we employed a formulation of pioglitazone in a biocompatible thermogel providing rapid, uniform and sustained inner ear drug delivery via transtympanic injection. Following noise exposure (120 dB, 10 kHz, 1h), different time schedules of treatment were employed: we explored the efficacy of pioglitazone given immediately (1h) or at delayed time points (24h and 48h) after noise exposure and the time course and extent of hearing recovery were assessed. We found that pioglitazone was able to protect auditory function at the mid-high frequencies and to limit cell death in the cochlear basal/middle turn, damaged by noise exposure. Immunofluorescence and western blot analysis provided evidence that pioglitazone mediates both anti-inflammatory and anti-oxidant effects by decreasing NF-B and IL-1 expression in the cochlea and opposing the oxidative damage induced by noise insult. These results suggest that intratympanic pioglitazone can be considered a valid therapeutic strategy for attenuating noise-induced hearing loss and cochlear damage, reducing inflammatory signaling and restoring cochlear redox balance.